Legal Monopolistic Practices as Unfair Business Competition in the Sales of Packaged Cooking Oils in Indonesia Maqashid Sharia Perspective (Study Decision No.15/Kppu-I/2022) - Muhammad Amin Siregar; Fauziah Lubis (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research analyzes cases of business competition violations in the sale of packaged cooking oil in Indonesia, related to unfair pricing. The Decision of the Business Competition Supervisory Commission (KPPU) Number 15/KPPU-I/2022 is the focus of the research, concerning Article 19 letter c of Law Number 5 of 1999. This research aims to produce KPPU results from the Maqashid Sharia perspective, especially in safeguarding assets and treasure (Hifz Al-Mal). In addition, this research examines the impact of violations on the availability and price of cooking oil in the Indonesian market. The research method used is normative juridical which is used to analyze statutory regulations, especially Law Number 5 of 1999, as well as related KPPU decisions which involve data analysis from books, journals, and literature relevant to cases of violations and Maqashid Sharia principles. The research results showed that seven companies were proven to have violated Article 19 letter c of Law Number 5 of 1999, by practicing limiting supply and creating artificial shortages that were detrimental to consumers. This violates the principles of Hifz Al-Mal, and is detrimental to the economy and social welfare. Implementation of a program that includes business competition which is expected to prevent similar violations and promote healthy business competition following Maqashid Sharia. However, the effectiveness of this program needs to be increased through massive outreach by KPPU. This research provides policy recommendations to create a fairer and more prosperous market in Indonesia.